Behavioral Change Interventions in Dental Hygiene for Prevention of Dental Caries in Children at SDN 09 North Pontianak (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
West Kalimantan has extensive peatlands, so its groundwater has a low calcium and fluorine content. The low content of these two minerals can make teeth susceptible to damage and affect the development of children's teeth. The high rate of dental caries in children requires intervention in order to change dental hygiene behavior and prevent further development of dental caries. Method: The intervention was carried out by training dental hygiene to first grade students of SDN 09 North Pontianak and their parents. This study used promotive and preventive approaches by training both parents and children on the proper way to do dental and oral cleaning. Routine training after school in small groups with the assistance of an instructor was held for the students. Parents then help and supervise the child when brushing their teeth at home twice a day and report it in the diary that has been prepared. Result: Behavioral changes including frequency, duration, tooth brushing technique, tongue cleaning, and oral cleaning after eating, were obtained after the intervention. An increase in teeth and mouth cleaning skills was found to be in line with a decrease in plaque value (PHP-M Index) from 29.66 to 16.39. Conclusion: Tooth-brushing training activities can improve children's ability to clean their teeth and mouth. A tooth-brushing diary can be a medium to remind children about when to brush their teeth. The role of parents is to increase children's motivation to develop dental and oral cleaning behavior.